Living on the Fringes of Life and Death: Somali Migrants, Risky Entrepreneurship and Xenophobia in Cape Town (African Human Mobility Review, 2021)
Since the 2008 attacks on African migrants, xenophobic violence has become aform of social agency for responding to increasing unemployment, destitutionand crime in South Africa. Africans living and operating businesses in urban andperi-urban areas are now objects of different forms of social violence, as they arerepeatedly blamed for unfulfilled political promises by the ANC-led government.One of most victimised African migrant communities is the Somali community,whose business activities in cities and townships are perceived as undesirablethreats to locals’ sources of livelihood. This article uses qualitative data collectedfrom 30 Somali migrants in Bellville and Khayelitsha, Cape Town to examine howSomalis’ co-existence with South Africans and their business tactics in Cape Townintersect to influence xenophobic violence. It explores the relationship betweenrisky entrepreneurship and xenophobia, and the threats that this relationshipposes to Somali lives.